Cancer de la thyroïde - BELFODIL, Amel (My University, 2023)
Thyroid cancer is most often a slow-growing cancer with a favorable prognosis. Thyroid cancer is a disease of the thyroid cells. It is rare, representing 1% of all cancers. Epithelial thyroid carcinomas of follicular origin represent the vast majority of thyroid tumors and medullary cancers developed from C cells represent approximately 5 to 8% of thyroid tumors. This work concerns the retrospective descriptive study of differentiated thyroid cancers carried out in the breast on 21 patient files (09 in 2021 and 12 in 2022) suffering from thyroid cancer. These data were obtained at the pathological anatomy and cytology department of Mostaganem University Hospital. The results obtained are submitted by the female sex representing a rate of 6.4% than the male sex. This study detected that 55% of tumors are micro-carcinomas, 35% of tumors are carcinomas and the remaining 10% are macro-carcinomas. Furthermore; All tumors concerning the population studied the most frequent histological type is the anaplastic type carcinoma is the most predominant with a rate of 78% from 2021 to 2022, however we can conclude that the epidemiology of surveillance contributes to a better knowledge of carcinoma thyroid allows good care of patients in Algeria. Thyroid cancer can occur at any age although it is common after age 30 and significantly more aggressive in older people.
Keywords: Thyroid cancers; tumors; Micro-carcinomas; anaplastic type